At Westonci.ca, we provide clear, reliable answers to all your questions. Join our vibrant community and get the solutions you need. Join our platform to connect with experts ready to provide accurate answers to your questions in various fields. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
To find the vertex of the quadratic function [tex]\( a(x) = (x-7)(x+3) + 25 \)[/tex], we will follow these steps:
### Step 1: Expand the Function
First, we need to expand the function to get it into the standard quadratic form [tex]\( ax^2 + bx + c \)[/tex].
[tex]\[ a(x) = (x-7)(x+3) + 25 \][/tex]
Let's expand [tex]\((x-7)(x+3)\)[/tex]:
[tex]\[ = x^2 + 3x - 7x - 21 \][/tex]
[tex]\[ = x^2 - 4x - 21 \][/tex]
Now we add the constant term 25:
[tex]\[ a(x) = x^2 - 4x - 21 + 25 \][/tex]
[tex]\[ a(x) = x^2 - 4x + 4 \][/tex]
### Step 2: Find the First Derivative
To find the vertex, we need to determine where the first derivative of the function is zero, since the vertex of a quadratic function occurs at the maximum or minimum point.
The first derivative of [tex]\( a(x) = x^2 - 4x + 4 \)[/tex] is:
[tex]\[ a'(x) = 2x - 4 \][/tex]
### Step 3: Solve for the Vertex
Set the first derivative equal to zero and solve for [tex]\( x \)[/tex]:
[tex]\[ 2x - 4 = 0 \][/tex]
[tex]\[ 2x = 4 \][/tex]
[tex]\[ x = 2 \][/tex]
So, the x-coordinate of the vertex is [tex]\( x = 2 \)[/tex].
### Step 4: Find the y-coordinate of the Vertex
Substitute [tex]\( x = 2 \)[/tex] back into the original function [tex]\( a(x) \)[/tex] to find the y-coordinate:
[tex]\[ a(2) = (2-7)(2+3) + 25 \][/tex]
[tex]\[ a(2) = (-5)(5) + 25 \][/tex]
[tex]\[ a(2) = -25 + 25 \][/tex]
[tex]\[ a(2) = 0 \][/tex]
Therefore, the y-coordinate of the vertex is [tex]\( y = 0 \)[/tex].
### Conclusion
The vertex of the function [tex]\( a(x) = (x-7)(x+3) + 25 \)[/tex] is at the point [tex]\( (2, 0) \)[/tex].
### Step 1: Expand the Function
First, we need to expand the function to get it into the standard quadratic form [tex]\( ax^2 + bx + c \)[/tex].
[tex]\[ a(x) = (x-7)(x+3) + 25 \][/tex]
Let's expand [tex]\((x-7)(x+3)\)[/tex]:
[tex]\[ = x^2 + 3x - 7x - 21 \][/tex]
[tex]\[ = x^2 - 4x - 21 \][/tex]
Now we add the constant term 25:
[tex]\[ a(x) = x^2 - 4x - 21 + 25 \][/tex]
[tex]\[ a(x) = x^2 - 4x + 4 \][/tex]
### Step 2: Find the First Derivative
To find the vertex, we need to determine where the first derivative of the function is zero, since the vertex of a quadratic function occurs at the maximum or minimum point.
The first derivative of [tex]\( a(x) = x^2 - 4x + 4 \)[/tex] is:
[tex]\[ a'(x) = 2x - 4 \][/tex]
### Step 3: Solve for the Vertex
Set the first derivative equal to zero and solve for [tex]\( x \)[/tex]:
[tex]\[ 2x - 4 = 0 \][/tex]
[tex]\[ 2x = 4 \][/tex]
[tex]\[ x = 2 \][/tex]
So, the x-coordinate of the vertex is [tex]\( x = 2 \)[/tex].
### Step 4: Find the y-coordinate of the Vertex
Substitute [tex]\( x = 2 \)[/tex] back into the original function [tex]\( a(x) \)[/tex] to find the y-coordinate:
[tex]\[ a(2) = (2-7)(2+3) + 25 \][/tex]
[tex]\[ a(2) = (-5)(5) + 25 \][/tex]
[tex]\[ a(2) = -25 + 25 \][/tex]
[tex]\[ a(2) = 0 \][/tex]
Therefore, the y-coordinate of the vertex is [tex]\( y = 0 \)[/tex].
### Conclusion
The vertex of the function [tex]\( a(x) = (x-7)(x+3) + 25 \)[/tex] is at the point [tex]\( (2, 0) \)[/tex].
We appreciate your time. Please revisit us for more reliable answers to any questions you may have. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.